Whole exome sequencing is an alternative method in the diagnosis of mitochondrial DNA diseases. Issue 6 (7th April 2022) - Sun, Chong; Wu, Shengyang; Chen, Ruiguo; Liu, Junwu; Wang, Jiasen; Ma, Yanyun; Yuan, Zhulin; Li, Yuezhen
Abstract: Background: Mitochondrial disease (MD) is genetically a heterogeneous group of disorders with impairment in respiratory chain complexes or pathways associated with the mitochondrial function. Nowadays, it is still a challenge for the genetic screening of MD due to heteroplasmy of mitochondrial genome and the complex model of inheritance. This study was designed to investigate the feasibility of whole exome sequencing (WES)‐based testing as an alternative option for the diagnosis of MD. Methods: A Chinese Han cohort of 48 patients with suspect MD features was tested using nanoWES, which was a self‐designed WES technique that covered the complete mtDNA genome and 21, 019 nuclear genes. Fourteen patients were identified with a single genetic variant and three with single deletion in mtDNA. Results: The heteroplasmy levels of variants in mitochondrial genome range from 11% to 100%. NanoWES failed to identify multiple deletions in mtDNA compared with long range PCR and massively parallel sequencing (LR‐PCR/MPS). However, our testing showed obvious advantages in identifying variations in nuclear DNA. Based on nanoWES, we identified two patients with nuclear DNA variation. One of them showed Xp22.33‐q28 duplication, which indicated a possibility of Klinefelter syndrome. Conclusion: NanoWES yielded a diagnostic rate of 35.4% for MD. With the rapid advances of next generation sequencing technique and decrease in cost, we recommend the usage of nanoWES as a first‐line method in clinical diagnosis. Abstract : Our study aims to explore the clinical usage of a WES product with broad coverage on both mitochondrial and nuclear genome in diagnosis of MD. We finally reach a diagnosis rate of 49%. With the fast development of NGS techniques and decreasing cost, we recommend the usage of nanoWES as a first‐line method in clinical diagnostic applications.